2013
DOI: 10.5152/dir.2013.047
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interoperator variability of lobar pulmonary volumes and emphysema scores in patients with chronic obstructive pulmonary disease and emphysema: comparison of manual and semi-automated segmentation techniques

Abstract: ORIGINAL ARTICLE PURPOSE We aimed to compare the intra-and interoperator variability of lobar volumetry and emphysema scores obtained by semi-automated and manual segmentation techniques in lung emphysema patients. MATERIALS AND METHODSIn two sessions held three months apart, two operators performed lobar volumetry of unenhanced chest computed tomography examinations of 47 consecutive patients with chronic obstructive pulmonary disease and lung emphysema. Both operators used the manual and semi-automated segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…As we expected, we found that right upper lobe and right middle lobe were major sources of relative variability (considering fissure) due to sharing of the other fissure (minor fissure) by visual observation, in agreement with the previous study [ 39 ]. Fissure analysis was not included as a part of algorithm in any of 4 programs that we used.…”
Section: Discussionsupporting
confidence: 93%
“…As we expected, we found that right upper lobe and right middle lobe were major sources of relative variability (considering fissure) due to sharing of the other fissure (minor fissure) by visual observation, in agreement with the previous study [ 39 ]. Fissure analysis was not included as a part of algorithm in any of 4 programs that we used.…”
Section: Discussionsupporting
confidence: 93%
“…This was true despite the frequent need for minor manual interventions to optimize lobe segmentation. This result is in accordance with a recent study of the interoperator agreement that used the same software (12). Conversely, this result partly contradicts another study in which the authors used a different software model that allowed only manual segmentation of the lobes, which indicates that the segmentation method used affects the reproducibility (8).…”
Section: Discussionsupporting
confidence: 88%
“…The relatively lower ICC for the lobar volume of the RML (ICC = 0.88) and larger confidence interval (0.84, 0.91) indicates the variance in identifying the right minor fissure. Based on the previous publication by Molinari et al [26], there is a relatively higher variability regarding the identification of the right minor fissure because it is connected with the right major fissure. A missing or indeterminate right minor fissure may cause difficulties in right lobe segmentation (Fig.…”
Section: Discussionmentioning
confidence: 99%